Eastern Caribbean Currency Union : 2007 Discussion on Common Policies of Member Countries; Staff Report; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Over the last decade, the Eastern Caribbean Currency Union (ECCU) macroeconomic performance has deteriorated relative to the rest of the Caribbean. Tourism accounts for three-fifths of exports, and the import content of consumption and investment is high. The ECCB-operated quasi-currency board arrangement (CBA) has continued to deliver price and exchange rate stability. The region has strong social indicators, but poverty, health, and crime remain concerns. Despite the implementation of ambitious revenue reforms, limited progress has been made toward fiscal consolidation. Credit has continued to expand rapidly.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet